2016
DOI: 10.1111/iwj.12653
|View full text |Cite
|
Sign up to set email alerts
|

A cost‐effectiveness analysis of optimal care for diabetic foot ulcers in Australia

Abstract: In addition to affecting quality of life, diabetic foot ulcers (DFUs) impose an economic burden on both patients and the health system. This study developed a Markov model to analyse the cost-effectiveness of implementing optimal care in comparison with the continuation of usual care for diabetic patients at high risk of DFUs in the Australian setting. The model results demonstrated overall 5-year cost savings (AUD 9100·11 for those aged 35-54, $9391·60 for those aged 55-74 and $12 394·97 for those aged 75 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(106 citation statements)
references
References 44 publications
(62 reference statements)
2
103
0
Order By: Relevance
“…For example, Australian studies have now demonstrated that the introduction of interdisciplinary DFD services have coincided with a halving of regional hospitalisation and amputation rates 13 . Further, a 2017 Australian cost‐effectiveness analysis reported that nationwide investments in access to evidence‐based DFD care 10 would not only improve patient outcomes, but after accounting for upfront investments would still save $10 000 per patient and $2.7 billion for the nation over 5 years 14 …”
Section: The Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Australian studies have now demonstrated that the introduction of interdisciplinary DFD services have coincided with a halving of regional hospitalisation and amputation rates 13 . Further, a 2017 Australian cost‐effectiveness analysis reported that nationwide investments in access to evidence‐based DFD care 10 would not only improve patient outcomes, but after accounting for upfront investments would still save $10 000 per patient and $2.7 billion for the nation over 5 years 14 …”
Section: The Solutionmentioning
confidence: 99%
“…The new strategy is the first comprehensive national evidence‐based DFD plan that describes in detail how health professionals, researchers and governments can implement actionable change now to ensure that all people with DFD have access to care; receive safe, quality, evidence‐based care; and benefit from research that continually strives to improve their care. Australian research has demonstrated that investments in these three priority areas may save 50% of all DFD hospitalisations and amputations, 13 and $2.7 billion to the Australian taxpayer over 5 years 14 . The new strategy describes how this can be done nationally to put us on the pathway to “ending avoidable amputations in a generation” 4…”
Section: The Call For Actionmentioning
confidence: 99%
“…Studies have demonstrated that evidence‐based care for chronic wounds improves clinical outcomes and is cost‐effective . However, economic models have been complicated by problems with input data.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated evidence from both clinical trials and cost‐effectiveness models favors a variety of different preventive, diagnostic, and treatment strategies in the area of diabetic foot diseases . A recent economic study from Australia revealed that optimal care saved A$9100.11 for those aged 35–54 years, A$9391.60 for those aged 55–74 years, and A$12 394.97 for those aged ≥75 years, with an additional 0.13, 0.13, and 0.16 QALYs, respectively, compared with usual care in an overall 5‐year time horizon . These total cost savings were estimated at A$2.7 billion over 5 years .…”
Section: Discussionmentioning
confidence: 99%
“…A recent economic study from Australia revealed that optimal care saved A$9100.11 for those aged 35–54 years, A$9391.60 for those aged 55–74 years, and A$12 394.97 for those aged ≥75 years, with an additional 0.13, 0.13, and 0.16 QALYs, respectively, compared with usual care in an overall 5‐year time horizon . These total cost savings were estimated at A$2.7 billion over 5 years . Economic evaluations from Sweden, the Netherlands and the UK have also shown that initiating adequate prevention strategies in all diabetic patients with would be cost‐effective or even cost‐saving by reducing the disease burden of amputation and/or foot ulcer .…”
Section: Discussionmentioning
confidence: 99%